Personality Viewed from the Psychology of Religion - K, Munawir; Maswar, Rezi; Rasela, Rasela; Aisyi, Nabila Rahadatul; Adila, Nesria; Ramdhan, Rizki M. (Suluah Pasaman, 2023)
Humans have various personalities that are different from each other. However, Allah SWT has gifted every human being with the same nature, where nature is in the form of spirit, body, and nafs. In the Islamic view, nature tends towards morals, but a person's habits, circumstances, and environment will later influence the formation of his personality. This research aims to explain the concept of personality from the perspective of religious psychology. This research uses a qualitative method with a content analysis approach, all data is taken from various sources originating from psychology books, religious psychology books, theories, and expert opinions. All data that has been collected is then analyzed thematically, in other words, the themes that have been obtained are described comprehensively and in-depth. To make it more interesting, all themes from the results of this research will be discussed with the results of studies by previous researchers and current psychological issues. This research found that personality psychology and religion are related to each other. Religious psychology plays a role in providing in-depth insight into religious values ​​that influence personality. The implications of this research are to provide reading material that helps readers understand it.